(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2010)
Historically, nature has been seen as beneficial to human wellbeing. Research has shown that there are a number of physical gains from contact with animals and there are a number of organisations that use animals as part of talking therapies. The present study explored five disabled adult horse-riders’ experiences of horse riding using interpretative phenomenological analysis (IPA). Five major themes are reported here (a) physical benefits, (b) psychological benefits, (c) interaction and relationship with horses, (d) drive and motivation and (e) negative aspects to riding. These themes support what the limited literature has found. The present study highlights a number of therapeutic benefits from contact with horses and suggests that psychology would profit from exploring how animals can be utilised in therapeutic settings.